Nickel 1,3,5-benzene-tricarboxylic acid-metal organic framework polymer composite saturable absorber for femtosecond pulse generation - Murad, Amir; Mohd Yusoff, Norita; Ying, Josephine Chyi Liew; Yaacob, Mohd Hanif; Goh, Chee Seong; Mahdi, Mohd Adzir (Elsevier, 2022)
This work demonstrates the fabrication of a saturable absorber with nickel 1,3,5-benzene-tricarboxylic acid (Ni-H3BTC)-metal organic framework (MOF) to generate soliton pulses in an erbium-doped fiber laser. The saturable absorber was fabricated by spin-coating Ni-H3BTC-MOF/polydimethylsiloxane composite on a tapered fiber as the encapsulation agent for light-matter interactions. The proposed cavity emitted a pulse laser at 1557.72 nm central wavelength with 3-dB bandwidth of 5.90 nm, pulse width of 907 fs, and average output power of 13.02 mW. At maximum pump power of 247.8 mW, the pulse energy was calculated to be 1.3 nJ at 10 MHz repetition rate. These results might assist as a footing to explore different types of available MOFs and their properties for the generation of ultrashort pulses.